Effects of Work Environment on Employee Job Satisfaction of Nepalese Commercial Banks - Parajuli, Kushal (Nepalese Journal of Business, 2025)
This study examines effects of work environment on employee job satisfaction of Nepalese commercial banks. Employee job satisfaction is the dependent variable. Similarly, the selected independent variables are physical environment, psychological environment, working hours, social work environment and motivation. The study is based on primary data with 129 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of effects of work environment on employee job satisfaction of Nepalese commercial banks. The study indicates that physical environment is positively correlated to employee job satisfaction indicating that better physical environment leads to increase in employee job satisfaction. Likewise, psychological environment is positively correlated to employee job satisfaction. This implies that better psychological environment leads to increase in employee job satisfaction. Similarly, working hour is positively correlated to employee job satisfaction. It indicates that appropriate working hours leads to increase in the level of employee job satisfaction. Similarly, social work environment is positively related to employee job satisfaction indicating that better social work environment leads to increase in employee job satisfaction. Further, motivation is positively correlated to employee job satisfaction which indicates higher the employee motivation, higher would be the employee job satisfaction.